Role of Stem-Cell Therapy in the Management of Amyotrophic Lateral Sclerosis, A Neurodegenerative Disorder: An Overview - SATYANAND TYAGI; SACHIN KUMAR; MOHIT SINGLA. (International Journal of Pharma and Bio Sciences, 2010)
Amyotrophic lateral sclerosis (ALS) is a syndrome marked by muscular weakness and atrophy with spasticity and hyperreflexia due to degeneration of the motor neurons of the spinal cord, medulla, and cortex. The symptoms of ALS include progressive weakness in the arms, legs, and trunk; and difficulty in talking, chewing, swallowing, and eventually breathing. The cause of disease is unknown, but the possibility of the illness being associated with a specific genetic defect holds promise of determining the course of the disease. Once this is done, it might be possible to treat the genetic abnormality. Genetically, there is no way to predict this disease prior to its occurrence. There is an effective therapy; however, patients often benefit from referral to occupational or physical therapy or both. In the present article, we have concentrated on clinical features, morphology, symptomatic approaches, and mainly role of stem cell therapy involved in the management of Amyotrophic lateral sclerosis. The aim of present article is to provide in depth knowledge about latest research going on in the field of stem cell therapy & its utility in the management of Amyotrophic lateral sclerosis.